KAJIAN MUTU BENIH TANAMAN JAGUNG PULUT (Zea mays ceratina L.) DI KABUPATEN BOLAANG MONGONDOW - Risky Sekoh; Selvie Tumbelaka; Adeleyda M.W Lumingkewas (Universitas Sam Ratulangi, 2021)
ABSTRACTwaxy corn or glutinous corn is a special type of corn that has a delicious taste, is more savory, fluffier andsofter. Seed quality consists of three components, namely: physical quality, physiological quality, geneticquality. This study aims to determine and study the quality of waxy corn seeds in Bolaang MongondowRegency. The research was conducted in Manado. This research took place from September to October 2020.This experiment used a completely randomized design (CRD), with 3 (three) treatments, namely the source ofwaxy corn seeds from several villages in Bolaang Mongondow Regency consisting of treatment P1 = seedsfrom the village Treatment Threshold P2 = Seed from Pusian Village Treatment P3 = Seed from Insil Village.Each treatment was repeated 4 (four) times in order to obtain 12 experimental units. Result of the experimentshowed The waxy corn in Ambang Village has a different quality from the quality of the seeds from PusianVillage and Insil Village. The quality of seed in Desa Ambang was characterized by germination rate of 88%,vigor index of 79%, synchronous growth of 86% and germinating speed of 28.44% / etmal. The seed qualityof Pusian Village is characterized by germination rate of 99%, vigor index of 83%, synchronous growth of98% and germinating speed of 31.53% / etmal and Village of Insil which has 100% germination, vigor indexof 83%, synchronous growth of 99% and speed of germination of 31.86 % / etmal.Keywords: Seed Quality, Pulut Corn